Review of therapies to increase the response of melanocytic activity to skin repigmentation of patients with vitiligo (Research, Society and Development, 2021)
Vitiligo is an immunological disease characterized by depigmentation of the skin, causing achromic spots, with no predilection for sex or ethnicity. Furthermore, it can cause emotional changes, compromise the individual's self-esteem and social relationships. Thus, this work proposes a systematic review of the literature aiming to evidence the efficiency of available therapy protocols for vitiligo and their correlation. Methodology: This is a systematic review study, descriptive and retrospective, carried out based on research in the main academic databases. Ex. PubMed, Lilacs and Capes Periodics, etc. Thus, free searches were made for words related to the proposed theme: vitiligo treatment and this associations, excluding studies that showed inefficiency (low percentage of repigmentation) when compared to conventional treatments. In this sense, 35 scientific articles and 27 different therapies for the treatment of vitiligo were found. Results and Discussion: Such therapies were divided into 4 categories: corticosteroids, photobiomodulation, immunosuppressants and antioxidants. The use of corticosteroids proved to be effective in stabilizing the disease. Phototherapies added kelina acted in 70% of the cases of repigmentation. JAK immunosuppressants demonstrated a total of repigmentation above 75%. And the antioxidants showed 67% efficacy of repigmentation, with emphasis on the species Polypodium leucotomos and Brosimum gaudichaudii with a high index of complete repigmentation, especially when associated with UVB radiation. Treatment with Ginko biloba had 80% disease stabilization. Conclusion: The protocols showed that the association of phototherapies with conventional and innovative therapies are more often effective in the treatment of vitiligo, enhancing the results.